Relationship between mode of sport training and general cognitive performance - Erik Chih-Hung Chang; Chien-Heng Chu; Costas I. Karageorghis; Chun-Chih Wang; Jack Han-Chao Tsai; Yung-Shun Wang; Yu-Kai Chang (Elsevier, 2017)
Purpose: To investigate whether athletes who engage in different modes of sports training correspondingly exhibit different patterns of performance on general cognition tasks. Methods: Sixty participants were recruited into an endurance, motorically complex, or control group, and were administered a series of physical tests and neuropsychological assessments. Results: Athletes in the endurance group demonstrated the highest levels of cardiovascular fitness and those in the motorically complex group exhibited the highest levels of motor fitness. Nonetheless, no differences in cognitive performance were observed between the 3 groups. Conclusion: These findings indicate that the mode of sport training, which results in either high cardiovascular or high motor fitness, bears no relationship to measures of general cognition in elite athletes. The present findings suggest that coaches and athletic trainers should be encouraged to monitor athletes' stress levels during training in order to maximize the beneficial effects of such training on general cognitive performance.